Prejudice and Religious Conflict : Dispositive Analysis of Film “Nama Saya Ahmad” - Dwi Wahyuni; Ahmad Ali Nurdin (Khazanah Theologia, 2022)
So far, studies on the sources of conflict are more dominantly viewed from a macro-social perspective without considering a micro-social perspective. Socio-cultural disparities, political dominance, inequality in economic distribution, and differences in religious or ethnic identity are more dominantly understood as causes of conflict. Whereas the potential for animal power that is inherent in humans is also a factor in the occurrence of conflict. Applying the method of dispositive analysis modeled by S. Jager and F. Maier, this text-based article aims to complete the lack of interpretation of the source of the conflict and analyze how the text of the film “Nama Saya Ahmad” represents the correlation of prejudice and religious conflict. This article shows that the film “Nama Saya Ahmad” depicts religious conflicts starting from prejudice between religious believers. In order for prejudice to be parsed, it is important to expand the dialogue space. Apart from breaking down prejudices, dialogue can also strengthen the social integration of the community.